Fabrication and 3D Patterning of Bio‐Composite Consisting of Carboxymethylated Cellulose Nanofibers and Cobalt Ferrite Nanoparticles. Issue 14 (15th April 2019) - Limaye, Mukta V.; Sahoo, Pradosh Kumar; Shirolkar, Mandar; Singh, Shashi B.; Khare, Amit; Shao, Yu‐Cheng; Chen, Kuan‐Hung; Qiu, Xian‐Sheng; Hsieh, Shang‐Hsien; Rana, Dhanvir Singh; Pong, W. F.
Abstract: In this work, flexible and free‐standing films of bio‐composite of carboxymethylated cellulose nanofibers (CMCNF) and cobalt ferrite (CFO) nanoparticles (NPs) have been fabricated using in‐situ chemical route. Control over CFO fraction (1% ‐ 25%) in CMCNF matrix was achieved by adjusting volume of the iron and cobalt precursors. Free‐standing films of CMCNF‐CFO bio‐composite were characterized using X‐ray diffraction, spectroscopic, microscopic, thermal and Magnetic measurements. The Raman and X‐ray absorption near edge spectroscopy studies confirms the formation of CFO in CMCNF matrix. The microscopic studies revealed that CMCNF fibers are decorated with CFO NPs having size of the order of ∼ 25 nm. Comparison of the thermal properties of CMCNF and CMCNF ‐CFO composites shows that thermal stability improves as CFO content increases. Finally, preliminary results on a method to create 3D patterns of CMCNF ‐CFO nanocomposite having lateral dimensions ∼1.2 μm were presented that pave the way to new uses of bio‐composites. Abstract : Bio‐composite of carboxymethylated cellulose nanofibers and cobalt ferrite nanoparticles fabricated by in‐situ synthesis method. Free‐standing and flexible films of the bio‐composite were obtained which have improved thermal stability compared to nanocellulose. The bio‐composite can be 3D patterned on silicon substrate, suggesting new opportunities for engineering biodegradable multifunctional systems.